A 5-Year Follow-up of Internet-Based Cognitive Behavior Therapy for Social Anxiety Disorder - Hedman, Erik (Gunther Eysenbach, 2011)
BACKGROUND: Internet-based cognitive behavior therapy (CBT) has been shown to be a promising method to disseminate cognitive behavior therapy for social anxiety disorder (SAD). Several trials have demonstrated that Internet-based CBT can be effective for SAD in the shorter term. However, the long-term effects of Internet-based CBT for SAD are less well known. OBJECTIVE: Our objective was to investigate the effect of Internet-based CBT for SAD 5 years after completed treatment. METHOD: We conducted a 5-year follow-up study of 80 persons with SAD who had undergone Internet-based CBT. The assessment comprised a diagnostic interview and self-report questionnaires. The main outcome measure was the Liebowitz Social Anxiety Scale-Self-Report (LSAS-SR). Additional measures of social anxiety were the Social Interaction Anxiety Scale (SIAS) and the Social Phobia Scale (SPS). Attrition rates were low: 89% (71/80) of the participants completed the diagnostic interview and 80% (64/80) responded to the questionnaires. RESULTS: Mixed-effect models analysis showed a significant effect of time on the three social anxiety measures, LSAS-SR, SIAS, and SPS (F (3,98) (-102) = 16.05 - 29.20, P < .001) indicating improvement. From baseline to 5-year follow-up, participants’ mean scores on the LSAS-SR were reduced from 71.3 (95% confidence interval [CI] 66.1-76.5) to 40.3 (95% CI 35.2 - 45.3). The effect sizes of the LSAS-SR were large (Cohen’s d range 1.30 - 1.40, 95% CI 0.77 - 1.90). Improvements gained at the 1-year follow-up were sustained 5 years after completed treatment. CONCLUSIONS: Internet-based CBT for SAD is a treatment that can result in large and enduring effects. TRIAL REGISTRATION: Clinicaltrials.gov NCT01145690; http://clinicaltrials.gov/ct2/show/NCT01145690 (Archived by WebCite at http://www.webcitation.org/5ygRxDLfK)